The Professionals' Perceptions and Reliance on AI for Writing Business English Message : A Mixed-Methods Study in Semarang, Indonesia - Dwiky Darmawan (ITScience (Information Technology and Science), 2026)
This mixed-methods study explores how young professionals in Semarang, Indonesia, view and depend on artificial intelligence (AI) tools when communicating with others. While the use of AI is growing in emerging economies, the correlation between professionals’ perceptions, their level of trust, and their actual reliance on AI for business communication is still not well understood. The research seeks to answer: How do young professionals in Semarang perceive and rely on AI for writing business communication, and what factors shape this correlation. This study employed a concurrent mixed-methods design. Quantitative data were gathered from 30 participants aged 17 to 33 using a 15-item, 5-point Likert scale (M = 52.97, SD = 7.14). Qualitative data were obtained through semi-structured interviews with three participants. The data analysis involved descriptive statistics, t-tests, ANOVA, Pearson correlation, and thematic analysis. The results revealed an overall favorable view of AI as a tool for writting business message, with notable differences based on gender and occupation—engineers and marketing professionals showed higher levels of dependency on AI. The qualitative analysis uncovered a theme of strategic